Student interaction characteristics during collaborative group testing - Giuliodori, Mauricio Javier (2009)
We used collaborative testing in a veterinary physiology course (65 students) to answer the following questions: 1) do students with individual correct responses or students with individual incorrect responses change their answers during group testing? and 2) do high-performing students make the decisions, that is, are low-performing students carried by high-performing peers? To address these questions, students first completed the exam in the traditional format as individuals. After completing the exam as individuals, students completed the same exam in groups of two. Finally, the same questions were discussed by the instructor and students (instructor feedback). We found that students with individual incorrect responses changed their answers during group testing more often than students with individual correct responses (odds ratio: 7.58, P , 0.01). Furthermore, student feedback was more beneficial when group members had different individual answers than when they had same individual answers (P , 0.05). In addition, when group members had different individual answers, more answers were changed to correct responses than to incorrect responses (77% vs. 23%, P , 0.01). It was more important to have the correct answer than to be the high-performing student, because the student with the correct response (being either the high- or low-performing student) generally prevailed (; 80% of the time, P 5 0.5). Finally, the positive effects of group testing (77% of total effects, P , 0.05) were due to students who changed their individual answer to the correct response after discussion with peers with the correct response and also with the incorrect individual response.